2012
DOI: 10.1016/j.marpol.2012.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and legal assessment of certified seafood

Abstract: Seafood counters used to be simpler places, where a fish was labeled with its name and price. Nowadays, it carries more information than a used-car listing. Where did it swim? Was it farm-raised? Was it ever frozen? How much harm was done to the ocean by fishing it?Many retailers tout the environmental credentials of their seafood, but a growing number of scientists have begun to question whether these certification systems deliver on their promises. The labels give customers a false impression that purchasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 7 publications
2
65
1
4
Order By: Relevance
“…Of all wild capture marine eco-labels, the MSC has likely been reviewed the most to determine its effectiveness in rebuilding marine fish stocks [33][34][35][36]. Froese et al reviewed several fisheries certified by the MSC and Friends of the Sea (FOS).…”
Section: Assumption Five-sustainable Fisheries Incentivized?mentioning
confidence: 99%
See 1 more Smart Citation
“…Of all wild capture marine eco-labels, the MSC has likely been reviewed the most to determine its effectiveness in rebuilding marine fish stocks [33][34][35][36]. Froese et al reviewed several fisheries certified by the MSC and Friends of the Sea (FOS).…”
Section: Assumption Five-sustainable Fisheries Incentivized?mentioning
confidence: 99%
“…Froese et al reviewed several fisheries certified by the MSC and Friends of the Sea (FOS). For stocks with available information, and defining overfished as stock size reduced below maximum sustainable yield, they found that 19% of the FOS and 31% of the MSC fisheries were overfished or subject to overfishing [33]. Agnew et al presented a rebuttal to this analysis.…”
Section: Assumption Five-sustainable Fisheries Incentivized?mentioning
confidence: 99%
“…Organization (IFFO), are becoming more numerous but are not yet producing sufficient amounts of fishmeal and oil to supply the eco-certified aquaculture sector. While outside the scope of this article, earlier study on eco-certification of capture fisheries (including forage fisheries) has revealed weaknesses in the content of the standards and also in the implementation and evaluation of certification schemes for capture fisheries (Jacquet et al 2010;Stokstad 2011;Froese and Proelss 2012). A focus on carnivorous species in eco-certification programs without addressing the feed issue at a more sectoral level could do more harm than good for the environmental performance of the sector.…”
Section: Discussionmentioning
confidence: 94%
“…Based on the recommendations of Froese and Proelss (2012) (Table 9), we noticed that due to variation in natural mortality from 0.91 yr -1 Pauly (1980) to 0.49 yr -1 Djabali et al (1994), the sardine stock in the central region of the Algerian coast changed from a state of not overfished and not overfishing to a state of overfished and overfishing (Table 9).…”
Section: Discussionmentioning
confidence: 99%